PERANCANGAN ARSITEKTUR ENTERPRISE UNTUK MENDUKUNG PROSES BISNIS MENGGUNAKAN TOGAF ARCHITECTURE DEVELOPMENT METHODE - Mulyanto, Yudi (Jurnal TAMBORA, 2017)
Construction and development of enterprise architecture and information systems are appropriately planned and well designed and suit to the needs and the abilities of the organization. Good planning will provide great benefits for construction and development of enterprise architecture, both in terms of human resources, budget and organization's readiness to implement the plan. In this study did not use all the phases of TOGAF ADM, this study only uses seven from nine phases TOGAF ADM namely the preliminary phase, architecture vision phase, business architecture phase, architecture of information systems phase, technology architecture phase, opportunity and solution phase and migration planning phase. The first phase of the enterprise architecture development is the prelimary phase, output from the preliminary phase becomes input to the early phases of the TOGAF ADM phases, which is named architecture vision phase and from that input device produced the new organizational structure that will be proposed. In the next phase of business phase was also analyzed using Value Chain analysis.